47 Hba1c testing in patients admitted with acute coronary syndromes identifies poor glycaemic control and facilitates new diagnoses of diabetes. (17th July 2020) - Williams, Howell; Kelshiker, Mihir; Mouy, Florence; Rendall, Alice; Sabin, Jodie; Thrower, Sally; Hui, Elaine; Raina, Tushar; Shah, Jaymin
Abstract : Background: Diabetes is a powerful but modifiable vascular risk factor, and it is well-established that effective glycaemic control improves cardiovascular outcomes. Current international guidelines do not recommend routine measurement of HbA1c in patients with acute coronary syndrome (ACS). We hypothesise that measuring HbA1c levels in all patients during admission to hospital with ACS would allow: Identification of patients with known diabetes and poor glycaemic control Increased diagnoses in patients with previously undiagnosed diabetes Aims: To identify how often HbA1c was measured in patients admitted with ACS, and when measured whether HbA1c identified poor glycaemic control in patients with known diabetes and/or led to new diagnoses of diabetes. Methods: Measurement of HbA1c was audited among patients admitted with ACS to two large acute NHS Trusts. Electronic records of patients admitted with ACS during a two-month period at Trust 1 and a three-month period at Trust 2 were analysed. Results: 218 patients were admitted with ACS (122/218 Trust 1, 96/218 Trust 2). Mean age was 71 (range 34-97), 70% male. 77/218 (35%) had known diabetes. HbA1c was measured during admission (or <3 months prior) in 51/218 (23%) of patients in total (37/122 [30%] in Trust 1 and 14/96 [15%] in Trust 2). 36/51 had known diabetes; in this population mean HbA1c was 68mmol/mol (range 39-121). Poor glycaemic control (HbA1c >64mmol/mol) was identified in 16/36 (44%) patients with known diabetes. 15/51 patients did not have known diabetes; in this population mean HbA1c was 40mmol/mol (range 31-50). HbA1c testing led to 1 new diagnosis of diabetes being confirmed. Among patients with known diabetes, 33/36 who had an HbA1c test underwent invasive angiography; 15/33 had an HbA1c >64mmol/mol and 18/33 HbA1c <64mmol/mol. The HbA1c >64mmol/mol population were more likely to undergo CABG than be managed with PCI or medical therapy alone than the HbA1c <64mmol/mol population (3/15 [20%] and 0/18 required CABG respectively, p=0.05). Comparing all patients with HbA1c >64mmol/mol (n=16) and HbA1c <64mmol/mol (n=35), there was no difference in length of stay. There were no in-hospital deaths and ACS re-admission rates were not significantly different (3/16 [19%] and 4/35 [11%] respectively, p=0.54) over mean 2.5 year follow-up Conclusion: In this study of patients admitted with ACS, HbA1c testing identified poor glycaemic control in a large number of patients with known diabetes. Only 1 new diagnosis of diabetes was made, likely due to established screening programs in primary care being effective in prior identification. Among patients with known diabetes, revascularisation with CABG was more common in those with poor glycaemic control in keeping with current revascularisation guidelines. HbA1c testing therefore identified a higher risk group within the ACS population, as well as identifying poor glycaemic control. These results, taken together with the recent development of novel therapies for diabetes, suggest that HbA1c testing should be considered routinely in all patients admitted with ACS. Conflict of Interest: None